The Study of Variation of Coefficient of Restitution on Subjecting the Bouncing Surface with A4 Paper - Karkee, R.; Gautam, S. (Kathmandu University Journal of Science, Engineering and Technology, 2014)
The coefficient of restitution (COR) of two colliding objects is the ratio of the relative velocity of separation to the relative velocity of approach. The coefficient of restitution varies from materials chosen. In this research we are interested in studying the variation of the coefficient of restitution by adding A4 paper on the bouncing surface where bouncing surface is the base for the ball bounce (example, thick plane plywood). We, then study the trend of the observed data i.e. we look at the nature of coefficient of restitution over the increasing number of A4 paper.